2020
DOI: 10.1016/j.brs.2020.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial focused ultrasound, pulsed at 40 Hz, activates microglia acutely and reduces Aβ load chronically, as demonstrated in vivo

Abstract: Objective: Iaccarino et al. (2016) [1] exposed 1 h of light flickering at 40 Hz to awake 5XFAD Alzheimer's Disease (AD) mouse models, generating action potentials at 40 Hz, activating~54% of microglia to colocalize with Ab plaque, acutely, and clearing~50% of Ab plaque after seven days, but only in the visual cortex. Hypothesis: Transcranially delivered, focused ultrasound (tFUS) can replicate the results of Iaccarino et al. (2016) [1] but throughout its area of application. Methods: We exposed sedated 5XFAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…[ 64,65 ] Moreover, MRIg‐FUS showed therapeutic efficacy per se on phosphorylated Tau and amyloid plaques. [ 66,67 ] In our exploratory study, brain accumulation and diffusion of the 19.3 kDa HPβCD were appreciably improved after only one application of FUS. Therefore, the combination of MRIg‐FUS with the i.v.…”
Section: Discussionmentioning
confidence: 80%
“…[ 64,65 ] Moreover, MRIg‐FUS showed therapeutic efficacy per se on phosphorylated Tau and amyloid plaques. [ 66,67 ] In our exploratory study, brain accumulation and diffusion of the 19.3 kDa HPβCD were appreciably improved after only one application of FUS. Therefore, the combination of MRIg‐FUS with the i.v.…”
Section: Discussionmentioning
confidence: 80%
“…The limited brain delivery and penetration was addressed employing MRIg-FUS, which has been shown to enhance the deposition of different drugs in various organs [57][58][59] while being well tolerated by animals [60][61][62][63] and humans [64,65]. Moreover, MRIg-FUS showed therapeutic efficacy per se on phosphorylated Tau and amyloid plaques [66,67]. In our exploratory study, brain accumulation and diffusion of the 19.3 kDa HPβCD were substantially improved after only one application of FUS.…”
Section: Discussionmentioning
confidence: 86%
“…As summarised above, it is clear that a reduction in gamma power is associated with AD pathology, at least in mouse models. Leveraging this knowledge, various invasive and non-invasive neuromodulation approaches have been adopted to modify AD pathology ( Table 2 ) [ 88 , 89 , 90 , 91 , 157 , 158 , 159 , 160 ]. For example, Tsai and her colleagues have elegantly demonstrated that both invasive and non-invasive gamma stimulations can ameliorate AD pathology [ 86 , 89 , 90 , 91 ]: optogenetic induction of gamma oscillations in the hippocampus can reduce amyloid load by activating microglia [ 89 ].…”
Section: Gamma Oscillations and Admentioning
confidence: 99%